What Is Cooking in the Pots of the Chiloe Archipelago? A Multiproxy Approach to Determine the Presence of Horticultural Groups - Reyes, Omar (2021)
What Is Cooking in the Pots of the Chiloe Archipelago? A Multiproxy Approach to Determine the Presence of Horticultural Groups Marine hunter-gatherers groups have occupied the northern-Patagonian channels since ~6000 yrs cal BP. Isotopic analyses of human remains plus lithic and faunal studies show that they have a strong marine diet with small variations toward the lateHolocene. In the last 300 years, post-European contact, there is a significant change in diet related to contact with other groups that carry pottery and domesticated species, that would have occurred ~ 1000 years cal BP, but with no direct archaeological evidence that refers to this important change in the cultural trajectories. To evaluate possible changes in the consumption of wild anddomesticated species and marine resources due to acquisition of this new technology, we carried out residue analysis of the pottery sherds, to see what old and new ingredients are being prepared in the ceramic vessels. The sample comes from sites of the Chiloe archipelago, ascribed to the prehispanic traditions, some related to the late ceramic period and others to the historical period. We shall compare these results with stable isotope studies and faunal, botanical and lithic assemblages of sites prior to this moment of contact to understand changes and social interactions between different social and cultural systems.